Effects of Self- Directed Learning and Collaborative Task Methods on Junior Secondary School Students’ Learning Outcomes in Social Studies in Oyo State (2014)
Social Studies teachers often use expository teaching and learning methods to teach the subject at Junior Secondary School level without recourse to innovative and interactive methods which are supposed to be used, in order to improve learning outcomes. There is dearth of quasi-experimental studies on self-directed learning and collaborative task methods which could enhance interactive learning in Nigeria. Available studies show that self-directed learning improved adult learning using non-experimental methods but not at the JSS level. Therefore, this study investigated the effects of self-directed learning and collaborative task methods on students‟ learning outcomes (achievement in Social Studies and critical thinking) in Oyo State, Nigeria. It also examined the moderating effects of gender and achievement motivation. The study adopted a quasi experimental design with a 4 X 2 X 2 factorial matrix in a nonrandomized pre-test, post- test, control group setting. Pre-test was given initially, post-test at the end of the treatment. A multistage sampling procedure was used to select 360 JSS 2 students (223 males and 137 females) from twelve public co-educational secondary schools in four Local Government Areas(LGA) in Oyo state, but 359 (223 males and 136 females) students eventually completed the study. Social Studies Achievement Test (KR20=0.80), Achievement Motivation Inventory (r=0.83) (30-60 low, 61-120 high), Students‟ Critical Thinking Inventory (r=0.87) (22-43 low, 44-88 high), were used. Descriptive statistics and Multivariate Analysis of Covariance (MANCOVA) were used for data analysis. Graphs were used to show the differences in the interaction effects. Treatment had significant main effect only on the dependent variable of achievement in Social studies. [Wilks‟ Λ = 0.90, F(6, 680) = 6.41, (p<0.05)]. The descending order of achievement among the participants was: Self-directed learning ( x =19.90), Self-directed learning and collaborative task method ( x =19.44), collaborative task method (=19.13). Gender had significant main effect on the combined dependent variables of achievement in Social studies and critical thinking [Wilks‟ Λ=0.97, (F(2,340) = 4.46,(p<0.05)]. Females had higher mean score in critical thinking ( x =59.37) than the males ( x =57.72) and in Social Studies achievement (Females = x = 19.39; Males = x = 18.43). Gender and achievement motivation had significant interaction effect on the combined dependent variables of achievement in Social studies and critical thinking, [Wilks‟ Λ=0.95, F(2,340) = 9.78, (p<0.05)]. However, critical thinking was affected more by the interaction of gender and achievement motivation after adjusting for covariance. [(F(1,341)=19.35, (p<0.05)], the associated univariate test of between-subject effects showed that treatment, [(F(3,341)= 13.13, p<0.05)], gender, [(F(1,341)=7.75, (p<0.05)], and achievement motivation, [(F(1,341)=10.09, (p<0.05)] affected significantly only achievement in Social studies. Self-directed learning and a combination of the methods as treatments in this study improved students‟ achievement in Social studies and critical thinking among sampled public JSS in Oyo State. Their use individually or collectively should be encouraged for the effective teaching and learning of Social studies. Male students should be motivated to achieve academically and be given the same opportunity irrespective of gender differences